2017
DOI: 10.1111/jpc.13629
|View full text |Cite
|
Sign up to set email alerts
|

Growth attenuation therapy for children with severe physical and cognitive disability: Practice and perspectives of New Zealand paediatricians

Abstract: This is the first study to investigate attitudes and practices of NZ paediatricians regarding GAT for severely disabled children. Results indicate a range of views but suggest that family requests for GAT do occur and that the majority of paediatricians are not opposed to GAT in the appropriate ethical and clinical context. The development of practice guidelines for GAT may lead to a more informed decision-making process about GAT for families and paediatricians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…Moreover, growth attenuation therapy administered together with hysterectomy, breast buds removal and appendectomy were intended to prevent scoliosis surgery, breast, uterine, or cervical cancer, to reduce the risk of inflammation of the appendix, as well as the pressure ulcers, bladder or lung infections that Ashley would be exposed to as a result of permanent immobilization (Ashley's Parents, 2007, pp. 4, 9-10;Gunther, Diekema, 2006;Kerruish, 2016, p. 73;Wrigley et al, 2017Wrigley et al, , p. 1181. It could be argued that the effects of Ashley treatment met the criteria of therapeutic treatment, such as: "maintenance or improvement of quality of life through relief of symptoms, pain and suffering"; "improvement of functional status or maintenance of compromised status"; "avoidance of harm to the patient in the course of care" (Jonsen, Siegler, Winslade, 2010, pp.…”
Section: Classification Of Medical Procedures: Therapeutic Versus Nonmentioning
confidence: 99%
“…Moreover, growth attenuation therapy administered together with hysterectomy, breast buds removal and appendectomy were intended to prevent scoliosis surgery, breast, uterine, or cervical cancer, to reduce the risk of inflammation of the appendix, as well as the pressure ulcers, bladder or lung infections that Ashley would be exposed to as a result of permanent immobilization (Ashley's Parents, 2007, pp. 4, 9-10;Gunther, Diekema, 2006;Kerruish, 2016, p. 73;Wrigley et al, 2017Wrigley et al, , p. 1181. It could be argued that the effects of Ashley treatment met the criteria of therapeutic treatment, such as: "maintenance or improvement of quality of life through relief of symptoms, pain and suffering"; "improvement of functional status or maintenance of compromised status"; "avoidance of harm to the patient in the course of care" (Jonsen, Siegler, Winslade, 2010, pp.…”
Section: Classification Of Medical Procedures: Therapeutic Versus Nonmentioning
confidence: 99%
“…Yet, the popular accounts above indicate that the publicity attracted by Ashley's case has generated a sizeable demand in the US, UK and elsewhere (e.g. Pilkington 2007, Field 2016, Wrigley et al 2018. In 2012 media reports suggested that at least twelve other instances of the treatment had occurred, with numbers potentially as high as one hundred globally (Pilkington 2012).…”
Section: The Legacy Of Ashley Xmentioning
confidence: 99%
“…Since only twenty-six percent of surveyed doctors responded, the number of actual interventions is likely to have been substantially higher (McGhee 2016). A 2016-17 study evidenced demand in New Zealand (Wrigley at al 2018), with five paediatricians having prescribed it and a further fifteen referring children elsewhere, including one to a clinician in the UK. More broadly, Curt Decker, director of the National Disability Rights Network (NDRN), suggested that thousands of families were actively exploring the possibility of the 'Ashley treatment' for their children (Bates 2012).…”
Section: The Legacy Of Ashley Xmentioning
confidence: 99%
See 2 more Smart Citations